Determination of formation constants and specific ion interaction coefficients for CanUO2(CO3)3(4−2n)− complexes in NaCl solution by time-resolved laser-induced luminescence spectroscopy. Issue 2 (13th December 2019) - Shang, Chengming; Reiller, Pascal E.
Abstract : The formation constants of CaUO2 (CO3 )3 2− and Ca2 UO2 (CO3 )3 (aq) were determined in NaCl medium at ionic strengths between 0.1 and 1 mol kgw −1 using time-resolved laser-induced luminescence spectroscopy (TRLS). Abstract : The formation constants of CaUO2 (CO3 )3 2− and Ca2 UO2 (CO3 )3 (aq) were determined in NaCl medium at ionic strengths between 0.1 and 1 mol kgw −1 using time-resolved laser-induced luminescence spectroscopy (TRLS). Spectroluminescence titration of UO2 (CO3 )3 4− complex by Ca 2+ were conducted at atmospheric CO2 (g) and varying pH values in order to eliminate the eventual precipitation of both schoepite (UO3  : 2H2 O) and calcite (CaCO3 ) in aqueous solutions. To identify the stoichiometry of calcium, the slope analyses corrected by the Ringböm coefficient for UO2 (CO3 )3 4− relative to pH and CO2 (g)—instead of typical expression relative to UO2 2+ and CO3 2− —was applied in this work. Satisfactory linear fits assessed the conditional stepwise formation constants in the range of ionic strength employed in this work, the values of which are in good agreement with literature data at comparable ionic strengths. Extrapolations to infinite dilution were realized in the framework of the specific ion interaction theory (SIT), also providing the evaluation of the specific ion interaction coefficients. The cumulative stability constants at infinite dilution was determined to be log10   β °(CaUO2 (CO3 )3 2− ) = 27.20 ± 0.04 and log10   β °(Ca2 UO2 (CO3 )3 (aq)) = 30.49 ± 0.05, which are in good agreement with extrapolation proposed elsewhere in literature using a different extrapolation framework. The specific ion interaction coefficients were found to be ε (CaUO2 (CO3 )3 2−, Na + ) = (0.29 ± 0.11) and ε (Ca2 UO2 (CO3 )3 (aq), NaCl) = (0.66 ± 0.12) kgw mol −1 . Integration of alkali metals into the ternary species may explain these positive and relatively large interaction coefficients. Implications on the speciation of uranium in clay groundwaters, representative of radioactive waste repositories, and in seawater are discussed.